Neuro-Endocrine Recovery After Pituitary Apoplexy: Prolactin as a Predictive Factor - Lammert, Alexander; Walter, Marc Sebastian; Giordano, Frank Anton; Al Zhgloul, Mansour; Krämer, Bernhard Karl; Nittka, Stefanie; Schulte, Dirk Michael; Ratliff, Miriam; Hänggi, Daniel; Seiz-Rosenhagen, Marcel (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective Pituitary apoplexy is a serious medical complication of a pre-existing pituitary adenoma characterized by a variety of clinical symptoms ranging from mild headache to neurologically impaired and finally comatose patients. Management options are surgery or conservative treatment (e. g., with dexamethasone). Surgery is commonly performed in case of severe acute neurological and visual symptoms. However, prospective studies demonstrating a benefit of surgery over conservative treatment in terms of visual, neurological and even endocrine outcomes are lacking. Decision making is still controversial, and recommendations for surgery are based on low evidence grades and focus on visual impairment. Endocrine function and especially markers identifying patients with potential for pituitary recovery after surgery are not well described in the literature.Patients and Design We analysed data from 24 patients (m:f/16:8) with a median age of 64 yrs (38 to 83yrs) that underwent surgery for pituitary apoplexy regardless of time from symptom onset. Apoplexies were necrotic in 14 cases and haemorrhagic in 10 cases.Results Preoperatively, 7 patients (29.2%) showed complete anterior pituitary insufficiency, 16 patients (66.6%) had partial anterior pituitary insufficiency and one patient (4.17%) had normal pituitary functions. Persistent panhypopituitarism was found in 7 patients (29.2%), whereas an overall improvement of pituitary function was noted in 13 (57.1%) patients. Preoperative prolactin (PRL) levels were significantly associated with recovery of endocrine functions, whereas specifically all patients with preoperative PRL levels of at least 8.8 ng/ml recovered partially or fully. Time to surgery (0–7 days vs. 1–4 weeks vs.>4 weeks) was not significantly associated with outcome.Conclusions Our data emphasize that normal and high preoperative PRL levels are associated with better endocrine outcome after surgery. We conclude that patients benefit from surgical intervention even after delayed diagnosis with the serum PRL levels is being a valid biomarker for clinical decision making.
Keywords: hypopituitarism; prolactin; hypocortisolism